Preparation method of composite hydrogel for promoting wound healing of burns and scalds as well as product and application of composite hydrogel
By using hydrogel matrix materials synthesized by sodium alginate and calcium chloride and loading copper-tin-sulfur nanosheets therein, a composite hydrogel dressing was prepared, which solved the problems of long healing cycles and scar formation in the treatment of burn and scald wounds, achieving the effect of promoting wound healing and antibacterial.
Patent Information
- Application Number
- CN202411671779.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
Existing medical dressings have adhesions, no healing, frequent dressing changes when treating burn wounds, resulting in a long healing cycle and easy scar formation.
A hydrogel matrix material synthesized using sodium alginate and calcium chloride as the main raw materials, and supported by copper-tin-sulfur nanosheets, was prepared by cross-linking reaction and hydrothermal method. The composite hydrogel forms a dressing with antibacterial and wound repair effects by slowly dropping the calcium chloride solution and adding copper-tin sulfur nanosheets.
This composite hydrogel significantly promotes the healing of burn and scald wounds, shortens the healing cycle, reduces scar formation, and has good antibacterial effects.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a composite hydrogel capable of promoting the healing of burn wounds, and its products and applications, and specifically relates to a hydrogel matrix material synthesized with sodium alginate and calcium chloride as main raw materials and copper tin sulfur nanosheets loaded in the matrix material, and explores the application of the composite hydrogel in promoting the healing of burn wounds. The present invention belongs to the field of nano-biomedical materials. Background Art
[0002] As a protective barrier, the skin is the largest organ of the human body. Skin burns and scalds occur frequently in daily life. If not handled properly, they may cause great harm to the human body. The healing period of burn wounds is long. If the treatment is not timely, scars will often form on the wound surface, which will affect the appearance and have a certain impact on people's quality of life, and even leave psychological shadows on patients. Common medical dressings are a type of medical material used for temporary coverage of various burn and scald wound surfaces. They can protect the wound surface from bacterial infection and other external factors, and play a role in protecting the wound and the wound surface. However, many problems will occur during the use of medical dressings, such as easy adhesion to the wound surface, no effect of promoting healing, frequent dressing changes, etc., which will further increase the burden on patients, and easily produce scars, causing great pain to the injured. Traditional hydrogel dressings are a gel-like substance applied to the burn wound surface. It can isolate the wound surface from the outside world, absorb the tissue fluid exuded from the wound surface in time, and isolate bacteria, fungi and viruses, thereby controlling infection and promoting wound healing. However, the antibacterial effect of the dressing is not ideal, and the healing period is not significantly shortened. Therefore, developing an antibacterial medical dressing that can effectively promote the healing of burn wounds is the research direction of burn repair products. Sodium alginate is a natural polymer material with excellent biocompatibility. Because the carboxyl group in the α-L-guluronic acid (G unit) in its molecular chain can cross-link with calcium ions to form a hydrogel, it has broad application prospects in food, biomedicine, tissue engineering, cosmetics and industry, and has therefore attracted much attention from academia and industry.
[0003] Previous studies have shown that copper ions have good antibacterial properties and the ability to promote wound repair. To this end, this study prepared alginate hydrogel by adding calcium chloride solution to sodium alginate aqueous solution for cross-linking reaction. Before gelation, copper, tin and sulfur nanosheets synthesized by hydrothermal method were added to prepare composite hydrogel, and then its application on burn wounds in mice was explored. Summary of the invention
[0004] The present invention aims to provide a method for preparing a composite hydrogel for promoting the healing of burn and scald wounds.
[0005] Another object of the present invention is to provide a composite hydrogel product prepared by the above method for promoting the healing of burn wounds.
[0006] Another object of the present invention is to provide an application of the above product.
[0007] The object of the present invention is achieved by the following scheme: a method for preparing a composite hydrogel for promoting the healing of burn wounds, wherein the composite hydrogel is a hydrogel matrix material synthesized with sodium alginate and calcium chloride as main raw materials, and copper tin sulfur nanosheets loaded in the matrix material, comprising the following steps: A 2wt.%~10wt.% sodium alginate aqueous solution was slowly added with a 1wt.%~6wt.% calcium chloride aqueous solution at a rotation speed of 500~1500 rpm. After the addition was completed, stirring was continued for 5 minutes to obtain a hydrogel matrix material calcium alginate hydrogel. Before the gelation, copper, tin and sulfur nanosheets synthesized by the hydrothermal method were added to prepare a composite hydrogel.
[0008] Preferably, the composite hydrogel is prepared according to the following steps: (1) Preparation of calcium alginate hydrogel: (11) After exposing the sodium alginate powder to ultraviolet light overnight for sterilization, 1 g of the powder was distributed in 20 ml of deionized water and stirred thoroughly to ensure that the sodium alginate was completely dissolved, thereby obtaining a sodium alginate aqueous solution; (12) After exposing calcium chloride powder to ultraviolet light overnight for sterilization, 1 g of the powder was distributed in 50 ml of deionized water and stirred thoroughly to ensure that the calcium chloride was completely dissolved, thereby obtaining a calcium chloride aqueous solution; (13) Take 4 ml of the prepared sodium alginate aqueous solution, slowly add 1 ml of the calcium chloride aqueous solution at a rotation speed of 1000 rpm, and continue stirring for 5 minutes after the addition is completed to obtain a calcium alginate hydrogel; (2) Preparation of copper, tin and sulfur nanosheet materials (21) 40 ml of N,N-dimethylformamide (DMF), 0.045 g of CuAc2, 0.054 g of SnCl4﹒5H2O, and 0.021 g of TAA were added to a three-necked flask in sequence; the flask was sealed and stirred in an oil bath at 150°C for 2 h; after the reaction was completed and cooled, the flask was transferred to the polytetrafluoroethylene liner of a reactor and polymerized at 220°C for 12 h to obtain copper-tin-sulfur nanosheets; (22) The copper, tin, and sulfur nanosheet materials were divided into centrifuge tubes and centrifuged at 8000r for 5 minutes. After removing the supernatant, acetone was added to the tubes and ultrasonicated at 50 Hz and 37°C for 5 minutes, and then the mixture was allowed to stand. After the supernatant was aspirated, acetone was added again to resuspend the mixture and centrifuged again. This step was repeated three times, and then the mixture was washed three times with deionized water. After drying in a drying oven, the mixture was subjected to ultraviolet disinfection to obtain the purified and disinfected copper, tin, and sulfur nanosheet materials. (3) Preparation of composite hydrogel During the stirring process of the calcium alginate hydrogel in step (13), the copper, tin and sulfur nanosheet material obtained in step (22) is slowly added and fully stirred and mixed to obtain the composite hydrogel.
[0009] The present invention also provides a composite hydrogel for promoting the healing of burn and scald wounds, which is prepared according to the above method.
[0010] The present invention also provides an application of the composite hydrogel in preparing a material for promoting the healing of burn and scald wounds.
[0011] The composite hydrogel was applied to the mouse burn wound dressing, and the performance of the dressing was tested according to the following steps: (1) Construction of mouse wound model: BALB-C mice were used for the experiment. The backs of the mice were depilated and disinfected. A 5g weight was then soaked in boiling hot water for 3 minutes and then taken out and placed close to the depilated area on the back of the mice for 15 seconds to construct the wound. (2) Use of materials to promote wound healing of burns and scalds: Dressings were applied to the wounds of each group of mice, and the wounds were covered with sterile surgical dressings for treatment. Each group of mice was housed in a single cage; (3) The weight of the mice was recorded every other day, and the wounds were cleaned with saline and photographed on the 1st, 4th, 7th, and 14th days of the experiment. The dressings were changed at the same time during the first three records.
[0012] (4) Immunohistochemistry and immunofluorescence analysis were performed on the wound tissues on days 3, 5, and 14 to examine the expression of CD68 and VEGF in the wound tissues, respectively.
[0013] The present invention uses sodium alginate and calcium chloride as the main raw materials to synthesize alginate hydrogels, and the raw materials used have high biological safety, and some of them are already commercial products. The present invention uses a hydrothermal method to synthesize copper, tin, and sulfur nanosheet materials. The preparation method is simple in process, low in cost, and highly operable, which can further meet production and application requirements. The animal experiment in the present invention adopts single cage breeding, and each group has repeated experiments and a long experimental period, so the data reliability is high.
[0014] The advantages of the present invention are: (1) The alginate hydrogel synthesized by the present invention uses sodium alginate and calcium chloride as main raw materials. The raw materials used have high biological safety, and some of them are already commercial products.
[0015] (2) The present invention adopts a hydrothermal method to synthesize copper, tin and sulfur nanosheet materials. The preparation method has simple process, low cost and strong operability, which can further meet the production and application requirements.
[0016] (3) The animal experiments in the present invention were conducted in single cages, each group underwent repeated tests, and the experimental period was long, so the data reliability was high. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The wound recovery images of mice treated in Examples 1, 2, and 3; Figure 2 This is an image of the wound healing rate of mice treated in Examples 1, 2, and 3; Figure 3 The images of weight changes of mice treated in Examples 1, 2, and 3; Figure 4 The images are of CD68 cytokine expression in the wounds of mice treated in Examples 1, 2, and 3; Figure 5 The images are of VEGF cytokine expression in the wounds of mice treated in Examples 1, 2, and 3; Figure 6 These are H&E staining images of the mouse organs treated in Examples 1, 2, and 3. DETAILED DESCRIPTION
[0018] The technical scheme of the present invention is further described below through specific examples. The following examples are further explanations of the present invention, but do not limit the scope of the present invention.
[0019] Experimental Example 1 The blank group was treated with only sterile surgical dressing covering the wound surface.
[0020] 1. Establishment of mouse scald model Step 1: Use 5 BALB / C mice of about 6 weeks old, anesthetize each mouse with 7% chloral hydrate, and then depilate and disinfect the back; Step 2: Soak a 5g weight in boiling hot water for 3 minutes, then take it out and place it close to the depilated area on the back of the mouse for 15 seconds to create a burn wound on the mouse.
[0021] 2. Treatment of burn wounds in mice Step 1: Cover the wound with a sterile surgical dressing for treatment. The mice were kept in single cages; Step 2: The weight of the mice was recorded every other day, and the wounds were cleaned with saline and photographed on the 1st, 4th, 7th, and 14th days of the experiment. During the first three records, the sterile surgical dressing was replaced at the same time.
[0022] Step 3: Perform immunohistochemistry and immunofluorescence analysis on the wound tissues on days 3, 5, and 14 to examine the expression of CD68 and VEGF in the wound tissues, respectively.
[0023] Step 4: On the 14th day after treatment, one mouse was anesthetized and then killed by cervical dislocation. The heart, liver, spleen, lung and kidney were obtained to make paraffin sections for HE staining and then observed under an optical microscope.
[0024] Example 2 In the calcium alginate hydrogel group, the wound surface was covered with a sterile surgical dressing on top of the calcium alginate hydrogel for treatment.
[0025] 1. A calcium alginate hydrogel is prepared according to the following steps (1) After exposing sodium alginate powder to ultraviolet light overnight for sterilization, 1 g of the powder is distributed in 20 ml of deionized water and stirred thoroughly to ensure that the sodium alginate is completely dissolved, thereby obtaining a sodium alginate aqueous solution; (2) After exposing calcium chloride powder to ultraviolet light overnight for sterilization, 1 g of the powder was distributed in 50 ml of deionized water and stirred thoroughly to ensure that the calcium chloride was completely dissolved, thereby obtaining a calcium chloride aqueous solution; (3) Take 4 ml of the prepared sodium alginate aqueous solution, slowly add 1 ml of the calcium chloride aqueous solution at a rotation speed of 1000 rpm, and continue stirring for 5 minutes after the addition is completed to obtain a calcium alginate hydrogel; 2. Establishment of mouse scald model Step 1: Use 5 BALB / C mice of about 6 weeks old, anesthetize each mouse with 7% chloral hydrate, and then depilate and disinfect the back; Step 2: Soak a 5g weight in boiling hot water for 3 minutes, then take it out and place it close to the depilated area on the back of the mouse for 15 seconds to create a burn wound on the mouse.
[0026] 3. Treatment of burn wounds in mice Step 1: Apply sodium alginate hydrogel dressing to the wound of mice, cover the wound with sterile surgical dressing for treatment, and keep them in single cages; Step 2: The weight of the mice was recorded every other day, and the wounds were cleaned with saline and photographed on the 1st, 4th, 7th, and 14th days of the experiment. The dressings were changed at the same time as the first three records.
[0027] Step 3: Perform immunohistochemistry and immunofluorescence analysis on the wound tissues on days 3, 5, and 14 to examine the expression of CD68 and VEGF in the wound tissues, respectively.
[0028] Step 4: On the 14th day after treatment, one mouse was anesthetized and then killed by cervical dislocation. The heart, liver, spleen, lung and kidney were obtained to make paraffin sections for HE staining and then observed under an optical microscope.
[0029] Example 3 In the composite hydrogel group, composite hydrogel was used as dressing and the wound surface was covered with sterile surgical dressing for treatment.
[0030] 1. A composite hydrogel is prepared according to the following steps (1) Preparation of calcium alginate hydrogel (11) Expose the sodium alginate powder to ultraviolet light overnight for sterilization, then take 1 g of the powder and distribute it in 20 ml of deionized water and stir thoroughly to ensure that the sodium alginate is completely dissolved; (12) Expose calcium chloride powder to ultraviolet light overnight for sterilization, then dispense 1 g of the powder into 50 ml of deionized water and stir thoroughly to ensure that the calcium chloride is completely dissolved; (13) Take 4 ml of the prepared sodium alginate aqueous solution, slowly add 1 ml of the calcium chloride aqueous solution at a speed of 1000 rpm, and continue stirring for 5 minutes after the addition is completed to obtain a calcium alginate hydrogel; (2) Preparation of copper tin sulfur nanosheets (21) Add 40 ml of N,N-dimethylformamide (DMF), 0.045 g of CuAc2, 0.054 g of SnCl4.5H2O, and 0.021 g of TAA into a three-necked flask in sequence; seal the flask and stir the mixture in an oil bath at 150 °C for 2 h; after the reaction is completed and cooled, transfer the mixture into a polytetrafluoroethylene liner and then place it in a reactor for high-temperature polymerization at 220 °C for 12 h to obtain copper-tin-sulfur nanosheets; (22) The copper, tin and sulfur nanosheets were divided into centrifuge tubes and centrifuged at 8000r for 5 min. After removing the supernatant, acetone was added and ultrasonicated at 50 Hz and 37°C for 5 min. The mixture was allowed to stand. The supernatant was then aspirated and acetone was added again to resuspend the mixture and centrifuged again. This step was repeated three times. The mixture was washed three times with deionized water and then dried in a forced air drying oven. After drying, the mixture was sterilized with ultraviolet light.
[0031] (3) Preparation of composite hydrogel While adding a calcium chloride aqueous solution dropwise to the sodium alginate aqueous solution while stirring, slowly adding the copper tin sulfur nanosheet material, and fully stirring and mixing to obtain the composite hydrogel; 2. Establishment of mouse scald model Step 1: Use 5 BALB / C mice of about 6 weeks old, anesthetize each mouse with 7% chloral hydrate, and then depilate and disinfect the back; Step 2: Soak a 5g weight in boiling hot water for 3 minutes, then take it out and place it close to the depilated area on the back of the mouse for 15 seconds to create a burn wound on the mouse.
[0032] 3. Treatment of burn wounds in mice Step 1: Apply composite hydrogel dressings to the wounds of mice, cover the wounds with sterile surgical dressings for treatment, and keep the mice in single cages; Step 2: The weight of the mice was recorded every other day, and the wounds were cleaned with saline and photographed on the 1st, 4th, 7th, and 14th days of the experiment. The dressings were changed at the same time as the first three records.
[0033] Step 3: Perform immunohistochemistry and immunofluorescence analysis on the wound tissues on days 3, 5, and 14 to examine the expression of CD68 and VEGF in the wound tissues, respectively.
[0034] Step 4: On the 14th day after treatment, one mouse was anesthetized and then killed by cervical dislocation. The heart, liver, spleen, lung and kidney were obtained to make paraffin sections for HE staining and then observed under an optical microscope.
[0035] Figure 1 The images of wound recovery of mice treated in Examples 1, 2 and 3 are shown. Example 3 has the best effect, followed by the calcium alginate hydrogel group, and the blank group has the worst effect.
[0036] Figure 2 The figures are the wound healing rates of the mice treated in Examples 1, 2 and 3. On the 14th day, the wound healing rate of the mice in Example 3 was 100%, and the wound healing rate of the mice in Example 2 was about 80%.
[0037] Figure 3 The weight change images of mice treated in Examples 1, 2, and 3 are similar.
[0038] Figure 4 The images are of CD68 cytokine expression in the wounds of mice treated in Examples 1, 2, and 3, which are the relative expression levels of CD68 in the wound tissues of the blank group on the third day, the seventh day, and the 14th day, respectively. On the 14th day, the blank group was still 100%, and the relative expression level of this Example 3 was less than 40%.
[0039] Figure 5 The images are of VEGF cytokine expression in the wounds of mice treated in Examples 1, 2, and 3. In the early stage of the experiment, the VEGF expression in Example 3 was the most significant, about 3.62 times that of Experimental Example 1. On the 14th day, the VEGF expression in Example 3 was still the highest.
[0040] Figure 6 These are H&E staining images of the mouse organs treated in Examples 1, 2, and 3. It can be seen that the organ tissues of the mice are in good condition after the experiment, that is, the mice in Experimental Examples 1, 2, and 3 are in good growth condition after treatment.
Claims
1. A method for preparing a composite hydrogel for promoting wound healing of burns and scalds, characterized in that: The composite hydrogel is a hydrogel matrix material synthesized with sodium alginate and calcium chloride as main raw materials, and the copper tin sulfur nanosheets loaded in the matrix material include the following steps: A 2wt.%~10wt.% sodium alginate aqueous solution was slowly added with a 1wt.%~6wt.% calcium chloride aqueous solution at a rotation speed of 500~1500 rpm. After the addition was completed, stirring was continued for 5 minutes to obtain a hydrogel matrix material calcium alginate hydrogel. Before the gelation, copper, tin and sulfur nanosheets synthesized by the hydrothermal method were added to prepare a composite hydrogel.
2. A method for preparing a composite hydrogel for promoting wound healing of burns and scalds according to claim 1, characterized in that Follow the preparation steps below: (1) Preparation of calcium alginate hydrogel: (11) After exposing the sodium alginate powder to ultraviolet light overnight for sterilization, 1 g of the powder was distributed in 20 ml of deionized water and stirred thoroughly to ensure that the sodium alginate was completely dissolved, thereby obtaining a sodium alginate aqueous solution; (12) After exposing calcium chloride powder to ultraviolet light overnight for sterilization, 1 g of the powder was distributed in 50 ml of deionized water and stirred thoroughly to ensure that the calcium chloride was completely dissolved, thereby obtaining a calcium chloride aqueous solution; (13) Take 4 ml of the prepared sodium alginate aqueous solution, slowly add 1 ml of the calcium chloride aqueous solution at a rotation speed of 1000 rpm, and continue stirring for 5 minutes after the addition is completed to obtain a calcium alginate hydrogel; (2) Preparation of copper, tin and sulfur nanosheet materials (21) 40 ml of N,N-dimethylformamide (DMF), 0.045 g of CuAc2, 0.054 g of SnCl4.5H2O, and 0.021 g of TAA were added to a three-necked flask in sequence; the flask was sealed and stirred in an oil bath at 150 °C for 2 h; after the reaction was completed and cooled, the flask was transferred to the polytetrafluoroethylene liner of a reactor and polymerized at 220 °C for 12 h to obtain copper, tin, and sulfur nanosheets; (22) The copper, tin, and sulfur nanosheet materials were divided into centrifuge tubes and centrifuged at 8000r for 5 minutes. After removing the supernatant, acetone was added to the tubes and ultrasonicated at 50 Hz and 37°C for 5 minutes, and then the mixture was allowed to stand. After the supernatant was aspirated, acetone was added again to resuspend the mixture and centrifuged again. This step was repeated three times, and then the mixture was washed three times with deionized water. After drying in a drying oven, the mixture was subjected to ultraviolet disinfection to obtain the purified and disinfected copper, tin, and sulfur nanosheet materials. (3) Preparation of composite hydrogel During the stirring process of the calcium alginate hydrogel obtained in step (13), the copper, tin and sulfur nanosheet material obtained in step (22) is slowly added, and the mixture is fully stirred to obtain the composite hydrogel.
3. A composite hydrogel for promoting the healing of burn wounds, characterized in that Prepared according to the method of claim 1 or 2.
4. Use of the composite hydrogel according to claim 3 in preparing a material for promoting healing of burn wounds.
5. The use according to claim 4, characterized in that: Application of materials to promote wound healing of burns and scalds in sterile surgical dressings.